From mere ‘stability’ to ‘durability’: revisiting intention dynamics from a self-regulatory perspective with intensive longitudinal methods - Jones, Christopher; Conner, Mark; Schüz, Benjamin Ernst Christoph (Applied psychology: health and well-being. Health and well-being, 2025)
Abstract Behavioral intentions predict behavior better if they are stable over time. A statistical argument suggests that this is due to less measurement error, but recent theoretical advances suggest self-regulatory effects: durable intentions remain temporally stable due to their persistence when faced with challenges. Here, we leverage intensive longitudinal data on adherence with non-pharmaceutical interventions (NPIs) during the COVID-19 pandemic (N?=?623; total assessments?=?19,740; study duration: 6 months each). We operationalize intention durability as temporal order-dependent variability (reversed root mean square of successive differences [RMSSD] between each valid assessment). We then examine the within- and between-person moderating effects of intention durability on the intention-behavior association as well as the effects of past on current behavior. In line with the theoretical assumptions, we find that more durable intentions are not only associated with a stronger intention-behavior link on a within- and a between-person level but also a stronger effect of past on current adherence with NPIs. Our findings support the hypothesized moderating effects of intention durability and provide a more nuanced understanding of the self-regulatory processes underlying the temporal stability of intentions.